Evidence-based practice: bibliometric review of national publications in nursing journals - Camargo, Fernanda Carolina (2017)
The objective of this research is to find studies about evidence-based Nursing practices in the Brazilian context, to identify themes, approaches to decision making and methodological approaches. It is a bibliometric revision in the databases LILACS, PubMed/MEDLINE, CINAHL and Scielo, including publications from 2000 on. The results were treated by frequencies and by the creation of meaning nucli to define the thematic approach to decision-making. 58 articles were obtained, most from 2009 to 2015 (n = 43), with thematic approaches: attention to individuals, family, community (32.14%); Nursing work process (17.86%); Training, education and teaching in nursing (5.36%); Concepts of evidence-based practice - EBP (16.07%); Instrumentalization for EBP (23.21%) and implementation of EBP (5.36%). The most frequent methods among the articles surveyed were: integrative revision and revision of the literature (n = 13 for each method). The expansion of these publications is contributing to the development of more judicious and safe practices, being crucial to EBP for Nursing as a profession, scientifically based.